2015
DOI: 10.1001/jama.2015.11068
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Intensive Care Unit Admission With Mortality Among Older Patients With Pneumonia

Abstract: IMPORTANCE Among patients whose need for intensive care is uncertain, the relationship of intensive care unit (ICU) admission with mortality and costs is unknown. OBJECTIVE To estimate the relationship between ICU admission and outcomes for elderly patients with pneumonia. DESIGN, SETTING, AND PATIENTS Retrospective cohort study of Medicare beneficiaries (aged >64 years) admitted to 2988 acute care hospitals in the United States with pneumonia from 2010 to 2012. EXPOSURES ICU admission vs general ward ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
132
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(144 citation statements)
references
References 37 publications
9
132
3
Order By: Relevance
“…There is strong clinical and physiologic plausibility that interventions considered as best practice with respect to short-term outcomes will also translate into improved long-term mortality and morbidity. Credible in-hospital interventions for which long-term consequences should be considered include (but are not limited to) (a) sepsis screening and detection strategies, (b) ICU triage and use of ICU, about which there is conflicting evidence in terms of short-term mortality in the United States and France, at least among elderly patients [173,174], (c) alternative antibiotic regimens, including empiric strategies, culture guidance, and de-escalation strategies, and the ABCDEF bundle [175]. Ultimately, however, our knowledge about the relationship between in-hospital interventions and long-terms outcomes is limited, which precludes any definitive statements about the impact of such interventions.…”
Section: Are There Potential In-hospital Interventions That Can Impacmentioning
confidence: 99%
“…There is strong clinical and physiologic plausibility that interventions considered as best practice with respect to short-term outcomes will also translate into improved long-term mortality and morbidity. Credible in-hospital interventions for which long-term consequences should be considered include (but are not limited to) (a) sepsis screening and detection strategies, (b) ICU triage and use of ICU, about which there is conflicting evidence in terms of short-term mortality in the United States and France, at least among elderly patients [173,174], (c) alternative antibiotic regimens, including empiric strategies, culture guidance, and de-escalation strategies, and the ABCDEF bundle [175]. Ultimately, however, our knowledge about the relationship between in-hospital interventions and long-terms outcomes is limited, which precludes any definitive statements about the impact of such interventions.…”
Section: Are There Potential In-hospital Interventions That Can Impacmentioning
confidence: 99%
“…In elderly patients hospitalized for pneumonia, the mortality rate is about 20%. 6 If pneumonia develops in patients already hospitalized for other conditions, mortality increase to 50-70%, and is higher in women than in men. 6 Pneumonia is the most common form of hospital-acquired infection.…”
Section: Epidemiologymentioning
confidence: 99%
“…6 If pneumonia develops in patients already hospitalized for other conditions, mortality increase to 50-70%, and is higher in women than in men. 6 Pneumonia is the most common form of hospital-acquired infection. Data from European Center Disease Control (ECDC), published in 2015, related to a survey conducted on 231,459 patients hospitalized between 2011 and 2012, identified 13829 patients (6.0%) with hospital infection.…”
Section: Epidemiologymentioning
confidence: 99%
“…A recent study of Medicare beneficiaries diagnosed with pneumonia found that ICU care was associated with lower adjusted mortality. 6 While ICU care has not been associated with reduced mortality in all-comer MI patients, 4 whether hemodynamically stable but higher risk patients specifically derive benefit has not been tested. It is also uncertain whether hospitals effectively triage NSTEMI patients at higher mortality risk to the ICU.…”
Section: Introductionmentioning
confidence: 99%